Stronger Arctic amplification from ozone-depleting substances than from carbon dioxide - Liang, Yu-Chiao; Polvani, Lorenzo M; Previdi, Michael; Smith, Karen L; England, Mark R; Chiodo, Gabriel (Environmental Research Letters, 2022)
Abstract Arctic amplification (AA)—the greater warming of the Arctic near-surface temperature relative to its global mean value—is a prominent feature of the climate response to increasing greenhouse gases. Recent work has revealed the importance of ozone-depleting substances (ODS) in contributing to Arctic warming and sea-ice loss. Here, using ensembles of climate model integrations, we expand on that work and directly contrast Arctic warming from ODS to that from carbon dioxide (CO 2 ), over the 1955–2005 period when ODS loading peaked. We find that the Arctic warming and sea-ice loss from ODS are slightly more than half (52%–59%) those from CO 2 . We further show that the strength of AA for ODS is 1.44 times larger than that for CO 2 , and that this mainly stems from more positive Planck, albedo, lapse-rate, and cloud feedbacks. Our results suggest that AA would be considerably stronger than presently observed had the Montreal Protocol not been signed.